Husband’s Knowledge And Support For The Implementation Of Early Initiation Of Breastfeeding In The Obstetric Room Of Timor Leste Referral Hospital - Riza Tsalatsatul Mufida; Maria De Fatima Moniz; Retno Palupi Yonni Siwi; Risna Zubaidah; Miftakhur Rohmah (Journal of Health Science Community, 2023)
The low practice of early breastfeeding is not due to many factors such as knowledge, husband’s support, action and education. Method: The method used is analytic correlational with a cross sectional approach. The number of samples was 20 post-partum mothers, the sampling method was with the Accidental sampling technique. The data analysis used was Chi Square to see whether there was a relationship and husband’s support for the implementation of early initiation of breastfeeding. Results: The results showed that of the 20 respondents, 13 respondents (65%) were good, 10 (50%) had good husband support, while implementing early initiation of breastfeeding was 14 (70%). The results of the Chi Square test show that the variables X1 and Y are 0.000, meaning that there is a relationship between Knowledge and the implementation of early initiation of breastfeeding.. For the results of the Chi Square test, the variables X2 and Y are 0.005, meaning that there is a relationship between husband’s support and the implementation of early initiation of breastfeeding. Conclusion The importance of maternal knowledge and husband’s support contributes greatly to postpartum early initiation of breastfeeding. in the Midwifery Room of the Suai Referral Hospital, Timor-Leste.